La cadena de valor de la ganadería bovina productora de carne de la región Tepalcatepec, del Estado de Michoacán - Bautista Hernández, Miguel Ángel (Universidad Michoacana de San Nicolás de Hidalgo, 2019)
The present investigation had the purpose of determining the relationships between variables that promote the value chain of bovine meat producers of the Tepalcatepec region. In this sense, in the general hypothesis of the research, it was suggested that the promotion of the value chain in its structure, behavior and function of beef cattle is determined by economies of scale, structural integration, institutional and regulatory framework, benchmarking, knowledge, innovation and governance. The collection of information was made through the application of a survey. The statistical analysis of the data obtained consisted in determining the measures of central tendency, frequency distribution, the Pearson correlation coefficient and the coefficient of determination. The results obtained account for an average possibility, to shape the value chain of cattle producing meat, because the responses of the different actors were located in a medium range. A deductive analysis is included on the effect of the value chain in regional development. It is also described and proposed what should be the value chain of bovine meat producers of the Tepalcatepec region, which promotes regional development. Finally, it is considered that in the study region more than a value chain, there are merely commercial relationships, which follow traditional procedures. So it is necessary to build a new business culture, which leads to a value chain. Allowing transformations in the behavior and functioning structure of the value chain that affect regional development.

La presente investigación tuvo la finalidad de determinar las relaciones entre variables que fomentan la Cadena de Valor (CV) de bovinos productores de carne de la región Tepalcatepec. En este sentido, en la hipótesis general de la investigación se planteó que el fomento de la CV en su estructura, conducta y funcionamiento de los bovinos productores de carne está determinada por las economías de escala, integración estructural, marco institucional y normativo, benchmarking, conocimiento, innovación y gobernanza. La recolección de la información se efectuó a través de la aplicación de una encuesta. El análisis estadístico de los datos obtenidos consistió en determinar las medidas de tendencia central, distribución de frecuencias, el coeficiente de correlación de Pearson (r) y el coeficiente de determinación (r2). Los resultados obtenidos dan cuenta de una posibilidad media, para conformar la CV de bovinos productores de carne, debido a que las respuestas de los diferentes actores se ubicaron en un rango medio. Se incluye un análisis deductivo sobre el efecto de la CV en Desarrollo Regional (DR), así mismo se describe y propone cuál debe ser la CV de bovinos productores de carne de la región Tepalcatepec, que promueva el DR. Finalmente se considera que en la región de estudio más que una CV, existen meramente relaciones comerciales, las cuales siguen procedimientos tradicionales, por lo que es necesario, construir una nueva cultura empresarial, que derive en una CV. Permitiendo transformaciones en la estructura conducta y funcionamiento de la CV que incidan en DR.
Instituto de Investigaciones Económicas y Empresariales. Doctorado en Ciencias del Desarrollo Regional
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/1500; info:eu-repo/classification/cti/5; ININEE-D-2019-0820; Región competitiva; Cadena de valor; Ganadería